The Biological Significance and Implications of Planar Cell Polarity for Nephrology - Papakrivopoulou, Eugenia; Jafree, Daniyal J.; Dean, Charlotte H.; Long, David A. (Frontiers in Physiology, 2021)
The orientation of cells in two-dimensional and three-dimensional space underpins how the kidney develops and responds to disease. The process by which cells orientate themselves within the plane of a tissue is termed planar cell polarity. In this Review, we discuss how planar cell polarity and the proteins that underpin it govern kidney organogenesis and pathology. The importance of planar cell polarity and its constituent proteins in multiple facets of kidney development is emphasised, including ureteric bud branching, tubular morphogenesis and nephron maturation. An overview is given of the relevance of planar cell polarity and its proteins for inherited human renal diseases, including congenital malformations with unknown aetiology and polycystic kidney disease. Finally, recent work is described outlining the influence of planar cell polarity proteins on glomerular diseases and highlight how this fundamental pathway could yield a new treatment paradigm for nephrology.